Teknologi untuk Meningkatkan Produktivitas dan Keuntungan Usahatani Ubikayu di Lahan Kering Ultisol - Budhi S. Radjit; Y. Widodo; N. Saleh; N. Prasetiaswati (Iptek Tanaman Pangan, 2014)
As a high producer of carbohydrate crop, cassava is suitable to be used for food, feed, and as raw materials for energy, food and non-food industries. Increasing food demand due to the increase of population, coupled with increasing feed and cassava based industries, have stimulated a sharp increases on the cassava demand, while the cassava production during the last ten years had increased by only 3.6% per year. To meet those demands, increasing cassava production through the expansion of harvested areas and improved productivity are required. Cassava in Indonesia, is mostly planted on Ultisol lands, which are distributed in Kalimantan, Sumatera, Maluku, Papua, and Sulawesi. Research on Ultisol in Natar South Lampung, Sulusuban Central Lampung, Kotabumi North Lampung, and Pekalongan East Lampung had identified cassava improved variety Litbang UK-2, Malang-6, Adira-4 and Kaspro as variety adapted to Ultisol. Production technique consisted of deep land preparation, 100 cm x 80 cm plant spacing, fertilization of kg urea, 200 kg SP36, 200 kg KCl, 500 kg dolomit, and 5 tons of cattle manure/ha, and herbicide weeding was reported to produce up to 60 tons of fresh cassava/ha, and to give profit up to Rp 38,456,000/ha, with the B/C ratio of 1.33 to 3.17. The technique was considered feasible to be developed in wider areas of Ultisols. Cassava production development requires the planting material production scheme, followed by promotion of new improved varieties and production technology. Capital support from the Government loan or fair cooperation with the investor giving gurantee for stable and fair prices is needed.